Реологические свойства фурано-эпоксидных реакционоспособных олигомеров - Рассоха, Алексей Николаевич (НТУ "ХПИ", 2013)
У статті детально розглянуті питання впливу складу фурано-епоксидних олігомерів на їх реологічні властивості. Зроблені висновки щодо структури і властивостей таких систем і можливості формування на їх основі захисних антикорозійних покриттів.

In this paper, the influence of furan-epoxy oligomers composition on their rheological properties is considered. The conclusions about the structure and properties of these systems and the forming corrosion protection coatings capabilities on the basis of these systems are described.
Rheological properties of furan-epoxy reactive oligomers
Keywords: полимерные композиционные материалы; олигомеры; реологические свойства; эпоксидные олигомеры; фурано-эпоксидные олигомеры